النظام القانوني للسلطة العليا للشفافية والوقاية من الفساد ومكافحته في الجزائر - سامية بهيجي; جويدة سمار (My University, 2024)
الملخص باللغة الانجليزية: In order to combat corruption crimes, Algeria has joined several international and regional agreements for international cooperation in the fight against corruption and its eradication, as well as to benefit from the experiences of countries in this field. In this regard, the Algerian state has dedicated many legal means and mechanisms, the most important of which is the issuance of Law 06-01 related to the prevention of corruption and the fight against it, which includes the creation of the National Authority for the Prevention of Corruption and the Fight Against It, which was enshrined under the constitutional amendment of 2016. According to the constitutional amendment of 2020, the constitutional founder changed its name to become the Supreme Authority for Transparency, Prevention of Corruption and the Fight Against It, and upgraded it from a consultative institution to a supervisory institution, and strengthened its position to the level of constitutional supervisory institutions by including it in the fourth chapter of the constitution under the title of supervisory institutions, to play its real supervisory role and get out of the inertia that it was in the past, and this was translated through the issuance of Law 22-08, which defines its organization and powers, and grants it financial and administrative independence, and provides it with a new and distinguished formation that includes personalities from different fields, and it has also been entrusted with many powers that combine prevention and combat, and it has been increased with a new structure in line with the powers entrusted to it, especially in the field of illicit enrichment. It has also become possible for it to notify the judiciary of all acts with a criminal description. Within the framework of its preventive role as the first constitutional task granted to it, it has recognized its consultative role represented in developing a national strategy for transparency that is concerned with preventing corruption, and the legislator has emphasized the principle of partnership through the involvement of all national actors in the prevention of corruption. ....................................... الملخص باللغة العربية: بهدف التصدي لجرائم الفساد، انضمت الجزائر إلى العديد من الاتفاقيات الدولية و الإقليمية من اجل التعاون الدولي لمحاربة الفساد ومكافحته وكذا الاستفادة من تجارب الدول في هذا المجال، وفي هذا الصدد كرست الدولة الجزائرية العديد من الوسائل القانونية والآليات لعل أهمها إصدار القانون 06-01 المتعلق بالوقاية من الفساد ومكافحته، الذي يتضمن انشاء الهيئة الوطنية للوقاية من الفساد ومكافحته، والتي تم تكريسها بموجب التعديل الدستوري 2016. وبموجب التعديل الدستوري 2020 غيّر المؤسس الدستوري تسميتها لتصبح السلطة العليا للشفافية والوقاية من الفساد ومكافحته، ورقاها من مؤسسة استشارية الى مؤسسة رقابية، وعزّز من مكانتها إلى مصاف المؤسسات الدستورية الرقابية من خلال إدراجها في الباب الرابع من الدستور تحت عنوان المؤسسات الرقابية، لتضطلع بدورها الرقابي الحقيقي وتخرج من دائرة الجمود الذي كانت عليه في السابق، وترجم ذلك من خلال صدور القانون 22-08 الذي يحدد تنظيمها وصلاحياتها، واعترف لها بالاستقلال المالي والإداري وتم تزويدها بتشكيلة جديدة ومتميزة تضم شخصيات من مجالات مختلفة، كما أوكلت لها صلاحيات عديدة تجمع بين الوقاية والمكافحة، وتم تزيدها بهيكلة جديدة تتماشى والصلاحيات الموكلة لها خاصة في مجال الإثراء غير المشروع، كما أصبح بإمكانها إخطار السلطة القضائية بكل الأفعال ذات الوصف الجزائي، وفي إطار دورها الوقائي بوصفها أول مهمة دستورية ممنوحة لها اعترف لها بدورها الاستشرافي المتمثل في وضع إستراتيجية وطنية للشفافية تُعنى بالوقاية من الفساد وأكد من خلاله المشرع على مبدأ التشاركية من خلال إشراك كل الفاعلين الوطنيين في الوقاية من الفساد. .................................